2022
DOI: 10.1002/nau.25046
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of factors that influence patient preference of third‐line therapy for overactive bladder

Abstract: Objective Patients with overactive bladder (OAB) refractory to first‐ and second‐line therapy may pursue third‐line therapies, including intradetrusor onabotulinum toxin‐A (BTX), peripheral tibial nerve stimulation (PTNS), and sacral neuromodulation (SNM). The factors that influence patient preference for each treatment modality have not yet been explored. This study sought to investigate the specific parameters that patients consider in choosing a third‐line therapy for OAB. Methods Patients refractory to fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In contrast, the current study was designed to evaluate a larger, more diverse sample of OAB patients compared to the prior study. The educational counseling on OAB therapies in the current study was provided within the survey as reading material rather than through a video interface as done in the prior study 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the current study was designed to evaluate a larger, more diverse sample of OAB patients compared to the prior study. The educational counseling on OAB therapies in the current study was provided within the survey as reading material rather than through a video interface as done in the prior study 4 …”
Section: Discussionmentioning
confidence: 99%
“…The educational counseling on OAB therapies in the current study was provided within the survey as reading material rather than through a video interface as done in the prior study. 4 In the first stage of our study, we investigated patient preferences for third-line therapies as currently delineated within the AUA/SUFU guidelines through text and pictorial descriptions of each therapy. Compared to our prior data on these preferences, this study found a similar pattern of patient preferences for third-line therapies, with BTX-A and PTNS having similar rates of interest, and SNM being chosen by fewer participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations